Lallemantia reylenne seeds as superdisintegrant: Formulation and evaluation of nimesulide orodispersible tablets - Malik, Karan; Arora, Gurpreet; Singh, Inderbir; Arora, Sandeep (International Journal of Pharmaceutical Investigation)
Aim: Orodispersible tablets also known as fast dissolving tablets disintegrate instantaneously within the mouth and thus can be consumed without water. The present study was aimed to formulate orodispersible tablets of nimesulide by using Lallemantia reylenne seeds as natural superdisintegrant. Materials and Methods: Powdered lallemantia seeds were characterized for powder flow properties (bulk density, tapped density, carr’s consolidation index, hausner ratio, angle of repose), swelling index, viscosity, pH, and loss on drying. The prepared tablets were evaluated for different tablet parametric tests, wetting time, water absorption ratio, effective pore radius, porosity, packing fraction, in vitro and in vivo disintegration time, in vitro dissolution and stability studies. Results and Discussion: Increase in Lallementia reylenne concentration had an appreciable effect on tablet hardness and friability which clearly indicated binding potential of the seeds. Water absorption ratio increased with increase in Lallemantia reylenne concentration from batch A1 to A4. Water uptake coupled natural polymer swelling could be the most probable mechanism for concentration dependent reduction in disintegration time by the Lallemantia reylenne seeds. Porosity of the formulated tablets was found to increase from batch A1-A4. The in vitro disintegration results were in line with in vivo disintegration results. Conclusion: It could be concluded that Lallemantia reylenne seeds could be used as natural superdisintegrant in the formulation of orodispersible tablets.
Keywords: Fast disintegrating tablets; Lallementia reylenne; superdisintegrant